If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + -4x = -10 Reorder the terms: 3(-6 + x) + -4x = -10 (-6 * 3 + x * 3) + -4x = -10 (-18 + 3x) + -4x = -10 Combine like terms: 3x + -4x = -1x -18 + -1x = -10 Solving -18 + -1x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -1x = -10 + 18 Combine like terms: -18 + 18 = 0 0 + -1x = -10 + 18 -1x = -10 + 18 Combine like terms: -10 + 18 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 18x^3-98x=0 | | 4(2-c)-5(2c+8)=-12 | | 3x-30=45-2x | | -39=-8(h+2)+3(2h-5) | | 321+123=444 | | 3p^2+5=8 | | 6c^2+17c+2=0 | | 8(19-x)=7(3x+1) | | 7=-5x+2x | | 3a^2-13a+4=0 | | 4g-6-g=3 | | 7xg=42 | | 16-2n-5+8n=67 | | 6ln(x-8)=1 | | 90=90p-90 | | -54=-32+w | | 111=x+68 | | 147n^4-84n^2+12= | | -9+12x-10-4x=8x-6x+46+1 | | g-35=-62 | | 8x+5=3-(9x-8) | | 0+8=8 | | r+53=-19 | | m+65=11 | | -3.6l=-71+34 | | n-75=42 | | 7lnx-3=8 | | x^2+16xy+64y^2= | | y+37=59 | | 34+-71=-3.61 | | f-25=35 | | -2m-1=1+2m |